(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Migration has increasingly been weaponized as a tool of hybrid warfare, challenging national security, legal frameworks, and humanitarian obligations. This article examines migration as a hybrid threat through a legal lens, focusing on recent trends in countering illegal migration and the implications of the Lithuania- Belarus border crisis. The article explores the strategic use of migration by state and non-state actors to destabilize target countries, assessing how hybrid threats manifest in border crises. It provides a legal analysis of state responses, including legislative measures, border control policies, and international legal obligations concerning asylum and human rights. The case study of the Lithuania- Belarus border crisis illustrates how irregular migration can be leveraged as a form of coercion, examining the legal justifications and challenges of Lithuania’s response, including pushbacks, emergency measures, and EU legal frameworks. Furthermore, the article discusses recent trends in countering illegal migration, highlighting developments in EU law, technological advancements in border management, and cooperative mechanisms among states. It evaluates the legal and ethical dimensions of restrictive measures, considering their compliance with international human rights law, the principle of non-refoulement, and European legal standards. By analyzing legal frameworks and state responses, the article aims to contribute to the broader discourse on security, migration law, and hybrid threats. It underscores the need for a balanced approach that upholds national security while adhering to international legal norms. The findings emphasize the necessity of legal adaptability in addressing evolving hybrid threats, ensuring that countermeasures remain both effective and lawful.